The Second Iteration Koch Curve Dipole Antenna with Movable Reflector - الشجيري، كاظم جواد; قنبر، خضير عباس (الجامعة المستنصرية - كلية التربية, 2015)
أنظمة الاتصالات التجارية والعسكرية الحديثة تحتاج هوائيات متعددة الأطوال الموجية، صغيرة الحجم، وبمقطع جانبي منخفض. في هذا البحث تم تحسين أداء التكرار الثاني لمنحني (Koch) لهوائي ثنائي القطب باستخدام عاكس متحرك. الهوائي المقترح مع العاكس يعمل بترددات رنينية (680، 1980، 3160و 4380 MHz). عند هذة الترددات (2> VSWR) ومعامل الانعكاس < -10 ديسبل وبعرض حزمة مقبولة وهي مفيدة في تطبيقات UHF/SHF. تم محاكات وتحليل الهوائي المقترح باستخدام برنامج 4NEC2.
Modern commercial and military communication systems need antennas with multi-band, small size and low profile. In this paper a performance of the second iteration Koch curve fractal dipole antenna is optimized by using a movable reflector. The proposed Antenna with reflector has operating resonant frequencies of (680, 1980, 3160 and 4380 MHz). at these frequencies VSWR < 2 and reflection coefficients < -10 dB with acceptable bandwidth which is useful in UHF/SHF applications. The proposed Antenna is simulated and analyzed using 4NEC2 software package.
Keywords: الهوائيات -- هندسة التليفزيون -- الهندسة الإلكترونية